Socio-Economic Nature and Specific Aspects of Management Methods - Jonibek Mambetsaliy ugli, Fayzullayev (American Journal of Economics and Business Management, 2024)
In this scientific article, the main reason for the innovative development of enterprises in our country today is the fact that the old methods of management are still not being abandoned, the emergence of new management methods over the last half century, and the most widespread of their work. system, total quality management, "definite time" management, time management, etc. are shown, industrial Proposals and recommendations were developed on the socio-economic nature and specific aspects of management methods, existing problems in practice and ways to eliminate them.